2016
DOI: 10.1111/vsu.12439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arthroscopic Lavage on Systemic and Synovial Fluid Serum Amyloid A in Healthy Horses

Abstract: Total protein, nucleated cell count, and percentage of neutrophils in synovial fluid were significantly increased after arthroscopic lavage; however, synovial fluid SAA was not affected by this procedure. Further research is warranted to validate synovial fluid SAA as a monitoring tool during treatment of septic arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 23 publications
(90 reference statements)
0
36
1
Order By: Relevance
“…Jacobsen et al [27] reported slightly increased plasma SAA values up to 5 days after arthroscopy (up to 100 mg/L), however these levels remain much lower than in the cases of the present study [26]. Sanchez-Teran et al [31, 32] recently suggested in their study that in healthy adult horses neither arthroscopic lavage nor through-and-through joint lavage with needles influenced plasma SAA concentrations 48–120 h after surgery. Moreover, Pollock et al [26] described that healthy horses undergoing an elective surgery responded similar to surgical trauma than horses with elevated plasma SAA concentrations undergoing emergency surgery.…”
Section: Discussioncontrasting
confidence: 60%
“…Jacobsen et al [27] reported slightly increased plasma SAA values up to 5 days after arthroscopy (up to 100 mg/L), however these levels remain much lower than in the cases of the present study [26]. Sanchez-Teran et al [31, 32] recently suggested in their study that in healthy adult horses neither arthroscopic lavage nor through-and-through joint lavage with needles influenced plasma SAA concentrations 48–120 h after surgery. Moreover, Pollock et al [26] described that healthy horses undergoing an elective surgery responded similar to surgical trauma than horses with elevated plasma SAA concentrations undergoing emergency surgery.…”
Section: Discussioncontrasting
confidence: 60%
“…68,69 Additionally, more recent studies have found that repeated arthroscopy and repeated through-and-through joint lavage also do not affect synovial or serum SAA concentrations, whereas the nucleated cell count and total protein are increased following these procedures alone. 70,71 Although most of the SAA found within synovial fluid may be an ultrafiltrate from plasma, a jointspecific isoform of SAA is produced by synoviocytes. 72 As in other diseases, bacterial infection of joints and other synovial structures seems to be the most potent stimulant of SAA production.…”
Section: Serum Amyloid a And Diseases Of Equine Joints And Synovial Smentioning
confidence: 99%
“…Intra‐articular injection of amikacin and repeat arthrocenteses of normal joints and tendon sheaths resulted in mild increases in synovial nucleated cell count, total protein, and percentage of neutrophils . However, SAA did not increase after arthroscopic lavage on healthy horses …”
Section: Introductionmentioning
confidence: 97%
“…Unfortunately, these tests are not readily available in clinical practice. As SAA did not increase after arthroscopic lavage in healthy horses, this test seems a good candidate to monitor septic arthritis, but further studies are needed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation